Differential aggressiveness of fungi implicated in esca and associated diseases of grapevine in France - C. Laveau; A. Letouze; G. Louvet; S. Bastien; L. Guerin-Dubrana (Phytopathologia Mediterranea, 2009)
We tested differences in the aggressiveness of six fungal species, Phaeomoniella chlamydospora, Phaeoacremonium aleophilum, Fomitiporia mediterranea, Eutypa lata, Diplodia seriata and Neofusicoccum parvum, all of which are associated with esca, Eutypa dieback or ‘black dead arm’ (BDA) of grapevines in France. Ten isolates per species (nine isolates for P. aleophilum), originating in various regions of France, were tested on rooted cuttings of cv. Cabernet Sauvignon by inoculating the mycelium of the species on wounds made in the vine wood. The inoculated plants were incubated in an open greenhouse and the experiment was repeated twice. The isolates were divided into three groups depending on the severity of the infection. Infection severity was based on the extent of the external cankers and the internal lesions, measured 5 and 15 months after inoculation, as compared with the controls. The fi rst group included all the P. chlamydospora and N. parvum isolates and two of the E. lata isolates. These isolates induced internal necrosis and external cankers developing from the point of inoculation. P. chlamydospora and N. parvum, produced large cankers and the longest internal lesions, and were the most virulent. The second group, comprising those E. lata isolates not in Group one and all isolates of D. seriata and of P. aleophilum, caused internal necrosis from which the vine afterwards totally healed. The third group included all the F. mediterranea isolates. These isolates caused the smallest lesions, generally not different from those in the controls, and developed a characteristic mycelium in the pith. No foliar symptoms were observed on any of the inoculated cuttings, except with the two E. lata isolates. Some seedlings displayed the typical foliar symptoms of Eutypa dieback. Different isolates within individual species exhibited signifi cant differences (P<0.05) in lesion development. This made it possible to select the most aggressive isolates for further study.